Amphotropic azobenzene derivatives with oligooxyethylene and glycerol based polar groups. Issue 42 (7th October 2015) - Tan, Xiaoping; Zhang, Ruilin; Guo, Chunxiang; Cheng, Xiaohong; Gao, Hongfei; Liu, Feng; Bruckner, Johanna R.; Giesselmann, Frank; Prehm, Marko; Tschierske, Carsten
Abstract : Amphiphilic azobenzenes self-assemble into double layer smectic and hexagonal columnar liquid crystalline phases, which are modified by protic solvents and light irradiation. Abstract : A series of amphiphilic azobenzenes with one to three lipophilic alkyl chains at one end and polar groups with oligooxyethylene (EO) and racemic 3-glyceryl units at the opposite end was synthesized and their thermotropic and lyotropic liquid crystalline self-assemblies were studied by POM, DSC and XRD. Tilted and non-tilted lamellar phases with interdigitated double layer structures (SmCd and SmAd, respectively) were found for the compounds with a single alkyl chain, whereas hexagonal columnar phases were formed by the compounds with two or three alkyl chains. The effect of protic solvents, like formamide, ethylene glycol and water, was investigated for representative examples. For the compounds with the single chain, induction and stabilization of SmA phases were observed, though broad regions of lyotropic SmC phases were retained in most cases. Depending on the structure of the polar group, the hexagonal columnar phases were either removed or drastically stabilized by the solvents. Photoisomerisation of an azobenzene chromophore was also studied.